THE PROSPECT OF JAPANESE NEW DIGITAL TECHNOLOGIES IN A SMART SOCIETY - Kuatova, Kh.R.; Ashinova, Zh.Ye. (Journal of Oriental Studies, 2024)
Japan, modernized in the 20th century, is a dynamically developed, promising country in the 21st century. Japan, which ranks second in economic terms after the United States, demonstrates a high level of technology. In addition, it is a country that has been able to improve its abilities and preserve its values even at the peak of the world’s development, having formed several thousand stories. Rapid changes and the development of new technologies have brought changes to our society and people’s daily lives. This article presents the opportunities and disadvantages of Japanese digital technologies, as well as their role in Japan’s creation of a smart society. At the same time, clear points of the 5.0 Society trend were studied not only in one direction, but also in different areas. Valuable virtual assistants such as the Internet of Things, artificial intelligence and robotics are shown as an example. Japan, being the country that laid the foundation for a smart society, has worked closely with several countries based on their experience. That is, the Society 5.0 technologies are considered an indispensable force for solving problems related to aging, population decline and major natural disasters. The transition from the information society to a more intelligent Japanese society has had an impact on maintaining a balance between virtual and real life for the Japanese. They were able to accept smart society without any obstacles. In the future, this smart society in Japan will undoubtedly create a smart world for Japanese society. Key words: Japan, Society 5.0, artificial intelligence, Internet of things, smart methods.